2014
DOI: 10.3201/eid2007.131587
|View full text |Cite
|
Sign up to set email alerts
|

Borrelia miyamotoisensu lato Seroreactivity and Seroprevalence in the Northeastern United States

Abstract: Serum from �%^4% of residents was positive for infection, compared with �%^9% for B. burgdorferi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
112
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(127 citation statements)
references
References 29 publications
10
112
1
4
Order By: Relevance
“…6 In these studies, 3.2% of patients suspected of Lyme borreliosis and up to almost 10% of patients with confirmed Lyme borreliosis had positive B. miyamotoi serology. Of note, 11% of B. miyamotoi seropositive sera were also positive for B. burgdorferi [80,81]. These findings were confirmed by a GlpQ-Luminex based study in the Netherlands, where a high seroprevalence to B. miyamotoi was found in forestry workers (10%) and patients with Lyme neuroborreliosis (7.4%) compared with 2% in blood donors [82].…”
Section: Reviewmentioning
confidence: 55%
See 1 more Smart Citation
“…6 In these studies, 3.2% of patients suspected of Lyme borreliosis and up to almost 10% of patients with confirmed Lyme borreliosis had positive B. miyamotoi serology. Of note, 11% of B. miyamotoi seropositive sera were also positive for B. burgdorferi [80,81]. These findings were confirmed by a GlpQ-Luminex based study in the Netherlands, where a high seroprevalence to B. miyamotoi was found in forestry workers (10%) and patients with Lyme neuroborreliosis (7.4%) compared with 2% in blood donors [82].…”
Section: Reviewmentioning
confidence: 55%
“…Two studies in the USA analyzed the seroprevalence of B. miyamotoi using an enzymelinked immunosorbent assay (ELISA) with confirmatory western blot to detect anti-GlpQ antibodies. In the healthy population, seroprevalence to B. miyamotoi was 0% in a nonendemic region and 1-3.9% in endemic regions (Table 1) [80,81]. One study [38] tested ticks from multiple states but did not clarify prevalences per state.…”
Section: Seroprevalence Of Anti-borrelia Miyamotoi Antibodies In Humansmentioning
confidence: 99%
“…The first cases of B. miyamotoi-infected humans were reported in Russia in 2011 [70,71]. A seroprevalence study of healthy residents of the Northeastern US showed (out of 639 samples), 25 (3.9%) people were exposed to B. miyamotoi and were antibody-positive and 60 (9.4%) were positive for B. burgdorferi antibodies [72]. An attachment study allowed transovarially-infected I. scapularis to blood feed on mice for 24, 48, 72, and 73-96 h [40].…”
Section: Borrelia Miyamotoi (Borrelia Myamotoi Disease Borreliosis)mentioning
confidence: 99%
“…Ezért magyarországi előfordulásával is számolni kell. Egyelőre sokkal több országban találtak a kullancsokban B. miyamotoi-t, mint amennyiben humán megbetegedést észleltek (1. és 3. táblázat [34][35][36][37][38][39][40]). Ez érthető, hiszen mind a klinikai, mind a laboratóriumi diagnózis nehézkes.…”
Section: Klinikum éS Epidemiológiaunclassified